MEMBANGKITKAN KEMBALI TRADISI DOLANAN ANAK SEBAGAI UPAYA PENANAMAN NILAI-NILAI KARAKTER DI SEKOLAH DASAR - SARI, MAYA KARTIKA (Pelita Bangsa Pelestari Pancasila, 2016)
Globalization and modernization has eroded the culture and traditions dolanan children are replaced by gadgets and other online games. Dolanan traditional children who are increasingly missing swallow the changing times, actually save a uniqueness, artistry and have usefulness for teamwork, motor skills, increase endurance and power of the brain, and cultivate positive moral values. Dolanan traditional children develop character values that are noble and moral messages such as shared values, cooperation, self-reliance, creative, love peace, honesty, responsibility, attitude gracefully (if you lose), communicative, encouragement of achievement, and obey the rules, social care and care for the environment. Therefore dolanan traditional children need to be developed and revived its existence so that the values of positive traits that lead to the noble personality.